Suitability, Efficacy, and Safety of Vernakalant for New Onset Atrial Fibrillation in Critically Ill Patients - Rudiger, Alain (Hindawi Publishing Corporation, 2014)
Objectives. This study investigates the suitability, safety, and efficacy of vernakalant in critically ill patients with new onset atrial fibrillation (AF) after cardiac surgery. Methods. Patients were screened for inclusion and exclusion criteria according to the manufacturers' recommendations. Included patients were treated with 3 mg/kg of vernakalant over 10 min and, if unsuccessful, a second dose of 2 mg/kg. Blood pressure was measured continuously for 2 hours after treatment. Results. Of the 191 patients screened, 159 (83%) were excluded, most importantly due to hemodynamic instability (59%). Vernakalant was administered to 32 (17% of the screened) patients. Within 6 hours, 17 (53%) patients converted to sinus rhythm. Blood pressure did not decrease significantly 10, 30, 60, and 120 minutes after the vernakalant infusion. However, 11 patients (34%) experienced a transient decrease in mean arterial blood pressure <60 mmHg. Other adverse events included nausea (n = 1) and bradycardia (n = 2). Conclusions. Applying the strict inclusion and exclusion criteria provided by the manufacturer, only a minority of postoperative ICU patients with new onset AF qualified for vernakalant. Half of the treated patients converted to sinus rhythm. The drug was well tolerated, but close heart rate and blood pressure monitoring remains recommended.